Design Analysis of PALF Natural Fiber Composite Laminate under Tensile Loading Condition using Simulation Approach - Raja Srikanth; Dr. Shaik Khadar Vali; Dr. K. Saraswathamma; S. Irfan Sadaq (International Journal of Fracture Mechanics and Damage Science, 2024)
Plant-based fibre reinforced materials are increasingly being employed for a variety of structural and non-structural purposes. Plant and animal-based fibres have different characteristics depending on a variety of circumstances. Mechanical qualities are primarily determined by parameters such as matrix, fillers, fibre content, fibre treatment, and fabrication techniques. The present work aim in analyzing the PALF natural fiber using simulation approach. In the process laminates are prepared as per ASTM standards in simulation software and tensile load is applied to study the behavior of laminate considering their deformation and stress. A variety of helix angle are chosen to study the same. From the observation it is observed that 60O and 90O are the optimum helix angle found the study where the deformation and strains are observed to be low when compared with other helix angles.
Keywords: Deformation; Helix angle; Natural Fiber; strain; tensile strength